Creatinine and Cystatin C: Markers of Poor Outcome in Critically Ill COVID-19 Patients? - Duarte André Ferreira; Rita Pinto Medeiros; Rita Rego; Ricardo Marinho; Elisabete Carolino; Aníbal Marinho (Publicações Ciência e Vida, 2023)
Introduction: Acute kidney injury is frequent in patients with COVID-19 and is associated with a higher mortality than in patients without acute kidney injury. Therefore we aimed to compare the creatinine and cystatin C initial values and trend in COVID-19 patients admitted to the Intensive Care Unit (ICU), in order to understand how renal dysfunction affects the prognosis. Methods: Longitudinal retrospective, single-center study of COVID-19 patients admitted to a tertiary care hospital ICU, between April 2020 and April of 2021. Demographic variables comorbidities, serum urea, creatinine, cystatin C values, as well as outcome were studied. Statistical analysis performed in SPSS 27. Results: The sample consists of 207 ICU patients, with mean age of 68 years, 68.6% male. Had chronic kidney disease, 11.5% (n=25) and the most prevalent comorbidities were hypertension, dyslipidemia and obesity. The median (interquartile range) length of stay at the ICU was 11 (6 - 19) days. The values of creatinine, cystatin C, urea adjusted for age and sex, at the time of hospital admission, were not significant for mortality. However, the variation in marker values between the first and second evaluation moments showed that a 5% increase in creatinine values increased, on average, the risk of death by about 2.3 times and a 5% increase in cystatin C values, increased, on average, the risk of death by about 2 times. Conclusion: The decline in renal function has a significant prognostic impact in patients with COVID-19. Therefore, an early detection of renal dysfunction in these patients is essential.